Feasibility and impact of Lynch syndrome genetic testing in newly diagnosed colorectal cancer patients: a multicenter observational study in Greece - S. Manolakou; N. Tsoukalas; E. Saloustros; T. Makatsoris; I. Boukovinas; A. Christopoulou; A. Karampeazis; I. Bompolaki; I.-I. Varthalitis; E. Voulgaris; K. Ballasis; A. Boutis; et al. (ESMO Gastrointestinal Oncology)
Background: Lynch syndrome (LS) is an autosomal dominant disorder associated with a heightened risk of specific cancers, caused by germline mutations in the mismatch repair (MMR) system, which leads to microsatellite instability (MSI). MSI-positive colorectal cancer (CRC) patients have an increased likelihood of LS. Despite this, LS germline genetic testing is not reimbursed by the National Health Authorities in Greece. To address this gap, the Hellenic Society of Medical Oncology (HeSMO) initiated a national program to screen and diagnose CRC patients with LS. Materials and methods: From 2017 to 2019, 151 newly diagnosed CRC patients in Greece were enrolled. MSI molecular analysis was carried out, followed by next-generation sequencing (NGS) germline testing in MSI patients without sporadic alterations to identify LS. Results: Of the patients, 76 (51.7%) exhibited MMR deficiency, with their tumors more likely to have mucinous histology (P < 0.001) and stage II disease (P = 0.015). Fourteen patients with MSH2, MSH6, or PMS2 deficiency directly underwent germline analysis, and all were positive for LS. Sixteen MSI patients (20.5%) had sporadic BRAFV600E mutations, and another 16 had MLH1 promoter hypermethylation. Of the remaining 32 patients tested for germline mutations, 8 were positive for LS, accounting for 15% of CRC patients—a 2.9-fold greater proportion than expected, according to historic records. Testing asymptomatic relatives identified two first-degree relatives with MSH2 mutations. Conclusions: These findings underscore the critical need for CRC-adapted preventive oncology and support the implementation of a national LS screening program in Greece, aligned with international guidelines.